2016
DOI: 10.1186/s13046-016-0312-4
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-tumor effects of Atractylenolide I on bladder cancer cells

Abstract: BackgroundAtractylenolide I (ATR-1), an active component of Rhizoma Atractylodis Macrocephalae, possesses cytotoxicity against various carcinomas. However, little is known about the effects of ATR-1on bladder cancer. In the present study, the anti-tumor activity of ATR-1 was examined on bladder cancer cells both in vivo and in vitro.MethodsMTT assay was used to assess the cytotoxic effect of ATR-1. Cell cycle distribution and apoptosis levels were evaluated using flow cytometry. Western blotting assay was appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 34 publications
4
71
1
Order By: Relevance
“…Atractylenolide 1 (ATL-1), ATL-2, and ATL-3 are the major bioactive components of medicinal herb Rhizoma Atractylodis Macrocephalae (Atractylodes macrocephala) and demonstrate anti-inflammatory and anticancer activities. However, the in-depth molecular mechanism underlying the anti-cancer effects of the major active compound, ATL-1, still remained unclear [8, 45, 48]. In the present study, we provided evidence demonstrating the anti-lung cancer effects of ATL-l.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Atractylenolide 1 (ATL-1), ATL-2, and ATL-3 are the major bioactive components of medicinal herb Rhizoma Atractylodis Macrocephalae (Atractylodes macrocephala) and demonstrate anti-inflammatory and anticancer activities. However, the in-depth molecular mechanism underlying the anti-cancer effects of the major active compound, ATL-1, still remained unclear [8, 45, 48]. In the present study, we provided evidence demonstrating the anti-lung cancer effects of ATL-l.…”
Section: Discussionsupporting
confidence: 64%
“…In the present study, we provided evidence demonstrating the anti-lung cancer effects of ATL-l. The doses of ATL-1 in the current study were similar or even lower than those reported by others demonstrating substantial anti-cancer responses in several cancer types [13, 45, 49]. Our results showed that ATL-1 inhibited lung cancer cell growth through ERK1/2-mediated suppression of Stat3 and SP1 protein expressions.…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…and exerts a wide range of pharmacological activities, including anti-inflammatory (11,12), anti-tumor (13,14) and anti-angiogenic effects (15). A previous study has implied a potential anti-depressive activity of AT-I (16).…”
Section: Introductionmentioning
confidence: 99%